2010
DOI: 10.4161/viru.1.5.12983
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides: The ancient arm of the human immune system

Abstract: The production of peptides and small proteins with microbicidal activity collectively called antimicrobial peptides (AMPs) is commonly considered to be a primitive mechanism of immunity and has been extensively studied in insects and other non-vertebrate organisms. In addition, a variety of AMPs present in amphibian skin secretion has been well characterised. There is now increasing evidence that AMPs play a crucial role in human immunity as well. Virtually all human tissues and cells typically exposed to micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
588
0
32

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 619 publications
(625 citation statements)
references
References 199 publications
(246 reference statements)
5
588
0
32
Order By: Relevance
“…Why Is the NCR247 [1][2][3][2][3][4] Peptide Unstable?-Our analysis showed that the NCR247 1-2,3-4 peptide remained stable after storage at ϩ4°C in the lyophilized form and Ϫ20°C when dissolved in water, providing further evidence that this is the naturally folded, stable state of the peptide. In contrast, although a single pure RP-HPLC peak was found for freshly synthesized NCR247 1-3,2-4 peptide, after storage, we observed multiple RP-HPLC peaks indicative of an unstable peptide.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Why Is the NCR247 [1][2][3][2][3][4] Peptide Unstable?-Our analysis showed that the NCR247 1-2,3-4 peptide remained stable after storage at ϩ4°C in the lyophilized form and Ϫ20°C when dissolved in water, providing further evidence that this is the naturally folded, stable state of the peptide. In contrast, although a single pure RP-HPLC peak was found for freshly synthesized NCR247 1-3,2-4 peptide, after storage, we observed multiple RP-HPLC peaks indicative of an unstable peptide.…”
Section: Discussionmentioning
confidence: 69%
“…RP-HPLC of the freshly synthesized and folded NCR247 1-3,2-4 peptide showed one major peak, indicating the presence of one pure peptide species (data not shown), as had been observed previously for newly prepared NCR247 1-2,3-4 (11). However, upon storage of the lyophilized peptide preparations, RP-HPLC of NCR247 1-3,2-4 resulted in multiple peaks whereas one major peak was still observed for NCR247 [1][2][3][4] (Fig. 2B).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…They are found throughout the tree of life (1,2). Taking advantage of the protein scaffold and the cellular equipment of transcription and translation, over evolutionary time scales antimicrobial peptides are mutable and often quite versatile, acquiring new functions as they strive to keep the host free from invaders (3).…”
mentioning
confidence: 99%